2015
DOI: 10.11646/phytotaxa.236.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Justicia paracambi, a new Brazilian species of Acanthaceae

Abstract: Justicia paracambi is described as a new, so far strictly endemic species to the state of Rio de Janeiro, which occurs in an area of natural forest in the Parque Natural Municipal do Curió, in the city of Paracambi. It differs from other Justicia L. species by the presence of dense glandular and non-glandular trichomes on the rachis, on the bracts and bracteoles and on the calyx, the terminal, lax panicle of spikes with decussate branches and flowers, the calyx 5-lobed, the white to greenish corolla and by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…[1][2][3] In Brazil, this genus is represented by approximately 128 species. 4 The species Justicia gendarussa Burm. F. is found in tropical and subtropical areas of Asia and India, and also in northeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In Brazil, this genus is represented by approximately 128 species. 4 The species Justicia gendarussa Burm. F. is found in tropical and subtropical areas of Asia and India, and also in northeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…5 Earlier phytochemical studies reported the presence of triterpenoids, 9 steroids, [9][10][11] flavonoides, [11][12][13] and nitrogen compounds in its leaves. 14,15 In this paper, we are describing the isolation and the structure elucidation of four new alkaloids, named Brazoides A-D (1)(2)(3)(4), of Justicia gendarussa (Figure 1). The structures were established by spectrometric techniques, mainly high-resolution electrospray ionization mass spectrometry (HRESIMS) and 1D and 2D nuclear magnetic resonance (NMR), including comparative analysis with literature values.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, o estudo afirma que o gênero é bioprodutor de alcalóides, o que indica, juntamente com as utilizações na medicina popular, um direcionamento de importância para pesquisas de aplicação das propriedades químicas do mesmo, fomentando a ampliação do conhecimento fitoquímico das espécies e sustentando, consequentemente, a elucidação de novos fármacos (Fernandes, 2016). Não foram encontrados estudos fitoquímicos de J. paracambi, pois é uma espécie descrita recentemente (Braz, 2015).…”
Section: Introductionunclassified
“…Currently, 17 species are recognized in this State (Flora do Brasil 2020). Thus, the discovery of new species is not surprising (Côrtes & Rapini 2011, Braz 2015, Silva & Kameyama 2019, Alcantara et al 2020. Furthermore, because of the several generic epithets synonymized under Justicia, some new combinations have been made (Graham 1988), but many are still necessary.…”
Section: Introductionmentioning
confidence: 99%